1993
DOI: 10.1111/j.1939-1668.1993.tb00072.x
|View full text |Cite
|
Sign up to set email alerts
|

An Experiential Framework for International Interior Design Education

Abstract: The purpose of this paper is, first, to present an experiential framework for an international interior design course and, second, to determine if this framework assisted the students in attaining the course goals. The course, European Design, is a study‐tour of five major cities in Europe. The experiential framework is based on Greenberg's (1978) four constructs of experiential learning as well as a fifth construct based on the authors' experience with international study programs. These constructs are well‐p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Traditional interior design education is primarily focused on didactic or "top-down" learning, in which the teacher is regarded as the source of predetermined knowledge that is transmitted to the student. In contrast, experiential approaches emphasize a learning environment in which students are given opportunities to explore and to build knowledge through direct engagement and independent problem-solving (Allison & Seaman, 2017;Guerin & Mason, 1993). Experiential learning is often regarded as making education more personally meaningful and relatable for students, and thereby more readily extending beyond the accumulation of facts to promote the transformation of worldviews and practices (Qualters, 2010).…”
Section: Experiential Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditional interior design education is primarily focused on didactic or "top-down" learning, in which the teacher is regarded as the source of predetermined knowledge that is transmitted to the student. In contrast, experiential approaches emphasize a learning environment in which students are given opportunities to explore and to build knowledge through direct engagement and independent problem-solving (Allison & Seaman, 2017;Guerin & Mason, 1993). Experiential learning is often regarded as making education more personally meaningful and relatable for students, and thereby more readily extending beyond the accumulation of facts to promote the transformation of worldviews and practices (Qualters, 2010).…”
Section: Experiential Learningmentioning
confidence: 99%
“…In a pedagogical sense, this type of reflective thought can help aspiring designers to integrate their knowledge and practice more fully, while also constantly pushing forward the horizons of the field and avoiding intellectual stagnation. Taking an experiential approach to design education is particularly useful because many aspects of design include creative practice, during which students and practitioners are called upon to continually forge innovative, meaningful, and effective solutions (Guerin & Mason, 1993). When engaging in experiential learning, students also have opportunities to reassess conventional knowledge in light of their own personal and cultural backgrounds, thereby incorporating a wider range of insights that can be expressed through their design work (Seaman & Nelson, 2011, p. 12).…”
Section: Experiential Learningmentioning
confidence: 99%
“…By knowing the context culture of the people, a designer can start understanding the preferences of the users. As reported by Guerin and Mason (Guerin & Mason, 1993), interior designers need to be culturally sensitive to face design challenges worldwide.…”
Section: Public Interest Statementmentioning
confidence: 99%
“…Black (2000) contends that internships help students identify and examine key business issues, which is a component of the Business Practices and Professionalism Standard (CIDA, 2018). Guerin and Mason (1993) suggested that international study can improve cultural sensitivity, which one could infer would figure heavily into a service-based domain. Moreover, CIDA standards mandate the demonstration of a global view relative to "social, cultural, economic, and ecological contexts" (CIDA, 2018, p. 16).…”
Section: Journal Of Interior Designmentioning
confidence: 99%